Transformational Leadership Model in Islamic Educational Institutions: A Comparative Study of Various Figures and Thoughts - Burhanuddin Burhanuddin (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
This research examines the application of transformational leadership models within Islamic educational institutions. It investigates the characteristics of transformational leadership, focusing on its relevance and effectiveness in fostering a positive learning environment and promoting holistic student development. The study employs a comparative approach, analyzing the leadership styles of influential figures in Islamic education, alongside exploring relevant theoretical frameworks and empirical studies. The methodology involves a literature review, comparative analysis, and synthesis of existing research to identify best practices and challenges. The findings highlight the significance of integrating Islamic values with transformational leadership principles, emphasizing the importance of visionary leadership, inspirational motivation, intellectual stimulation, and individualized consideration. The research identifies a gap in the literature regarding the specific contextualization of transformational leadership in Islamic educational settings. The study concludes with recommendations for future research and practical implications for educational leaders aiming to enhance the effectiveness of Islamic educational institutions.